Evaluation of the use of Antihypertensive Drugs in Outpatient Hypertension Patients at the Lasinrang Regional General Hospital, Pinrang Regency in 2023 - Yuliana, Dewi; Agus, Asfira; Azizah, Rizqi (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2024)
Hypertension is a complex condition in which blood pressure is permanently above normal. Hypertension is an increase in systolic blood pressure of more than equal to 140 mmHg and diastolic more than equal to 90 mmHg. This study aims to identify how antihypertensive drugs are used in hypertensive patients at the Lasinrang Regional General Hospital, Pinrang Regency. This study is a non-experimental research with a descriptive design taken retrospectively. The sample in this study is all outpatients with a diagnosis of hypertension at the Lasinrang Regional General Hospital in 2023. The sampling technique used is purposive sampling. The sample of this study is medical record data on hypertension patients in 2023 which is adjusted to the inclusion criteria. The results of the study showed that from 83 samples consisting of 50 women and 33 men, all of which met the inclusion and exclusion criteria, and showed a prevalence of age that dominated around 58-65 years (49,40%). In the evaluation of drug use, outpatient hypertension patients at the Lasinrang Regional General Hospital, Pinrang Regency had an indication accuracy of 100%, 100% drug accuracy, and 100% dose accuracy.